'Pressure fatigue': the influence of sap pressure cycles on cavitation vulnerability in Acer negundo. (25th February 2019) - Umebayashi, Toshihiro; Sperry, John S; Smith, Duncan D; Love, David M
Abstract: Vulnerability-to-cavitation curves (VCs) can vary within a tree crown in relation to position or branch age. We tested the hypothesis that VC variation can arise from differential susceptibility to the number of diurnal sap pressure cycles experienced. We designed a method to distinguish between effects of cycling vs exposure time to negative pressure, and tested the influence of sap pressure cycles on cavitation vulnerability between upper and lower branches in Acer negundo L. trees using static and flow centrifuge, and air-injection methods. Branches from the upper crown had greater hydraulic conductivity and were more resistant to cavitation than branches from the lower crown. Upper branches also showed little change after exposure to 10 or 20 pressure cycles between –0.5 MPa and –2.0 MPa. Lower branches, however, showed a marked increase in vulnerability to cavitation after pressure-cycling. This result suggests that 'cavitation fatigue' can occur without the actual induction (and reversal) of cavitation as documented previously, but simply from the cycling of pressures in the sub-cavitation range. This 'pressure fatigue' may explain age-related shifts in VCs that could eventually induce dieback in suppressed branches or trees. Pressure fatigue may help explain developmental variation in hydraulic capacity of branches within individuals.